2014
DOI: 10.1016/j.apradiso.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution characterization of a X-ray microCT system

Abstract: We report on an experimental characterization of the spatial resolution of a commercial X-ray micro-computed tomography scanner. We have measured the full modulation transfer function (MTF) to assess the spatial resolution. The MTF and those spatial frequencies corresponding to a contrast loss of 50% were determined as a function of different applied X-ray tube parameters and magnification-dependent pixel sizes. A significant influence of the focal spot enlargement on the achievable spatial resolution could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…Second, we aim to retain the full image resolution and quality during the basis material decomposition process. In microCT imaging, true spatial image resolution is often limited by pixel size, at least for low magnifications (Rueckel et al, 2014). Thus, we focussed on optimizing methods for image filtering and volume image registration.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we aim to retain the full image resolution and quality during the basis material decomposition process. In microCT imaging, true spatial image resolution is often limited by pixel size, at least for low magnifications (Rueckel et al, 2014). Thus, we focussed on optimizing methods for image filtering and volume image registration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is worthwhile to assess the image quality of the CBCT device and other radiographic imaging system quantitatively to ensure the diagnostic accuracy of the chosen modality [28]. Spatial resolution, which is related to the ability of distinguishing two adjacent structures on a radiograph, is one of the parameters, which can be measured objectively allowing us to estimate the imaging performance of an X-ray based medical system [29,30]. There are two main methods for determining the spatial resolution, namely visual resolution assessment test and MTF determination.…”
Section: Introductionmentioning
confidence: 99%
“…Brüllmann et al [29] found in their review, that there is a large variance between the values of observer based visual assessment and the quantitative MTF determination. In addition, numerous studies focusing on MTF measurements as a possible way for quantitatively evaluate the X-ray based imaging devices using cone-beam geometry [28,30,33,[35][36][37]. The image quality and consequently spatial resolution is influenced by several other factors such as focal spot size, overall geometry, tube voltage, tube current, exposure time, rotation arc, the size of field of view (FOV) and the reconstruction parameters as well as the image noise and the movement of the object [7,29,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, sufficient radiation intensities are necessary to achieve adequate signal-to-noise ratios. These two image quality criteria, which are contrarily related to the tube power, need to be well balanced in a sample specific way" [123].…”
Section: Introductionmentioning
confidence: 99%